Effect of cognitive load and emotional valence of distractors on performance during sleep extension and subsequent sleep deprivation. Issue 8 (4th February 2020) - Alger, Sara E; Brager, Allison J; Balkin, Thomas J; Capaldi, Vincent F; Simonelli, Guido
Abstract: Study Objectives: The purpose of the present study was to assess the extent to which sleep extension followed by sleep deprivation impacts performance on an attentional task with varying cognitive and attentional demands that influence decisions. Methods: Task performance was assessed at baseline, after 1 week of sleep extension, and after 40 h of total sleep deprivation. Results: One week of sleep extension resulted in improved performance, particularly for high cognitive load decisions regardless of the emotional salience of attentional distractors. Those who extended sleep the most relative to their habitual sleep duration showed the greatest improvement in general performance during sleep extension. However, a higher percentage of time spent in slow-wave sleep (SWS) on the last night of the sleep extension phase was negatively correlated with performance on more difficult high cognitive load items, possibly reflecting a relatively higher level of residual sleep need. Sleep deprivation generally resulted in impaired performance, with a nonsignificant trend toward greater performance decrements in the presence of emotionally salient distractors. Performance overall, but specifically for high cognitive load decisions, during total sleep deprivation was negatively correlated with longer sleep and higher SWS percentage during subsequent recovery sleep. Conclusions: The present findings suggest two possibilities: those who performed relatively poorly during sleep deprivation were more vulnerable because (1) they utilized mental resources (i.e. accrued sleep debt) at a relatively faster rate during wakefulness, and/or (2) they failed to "pay down" pre-study sleep debt to the same extent as better-performing participants during the preceding sleep extension phase.